Comparison of histology activity index scores in patients with HBeAg positive and HBeAg negative CHB to see difference in severity of liver injury - Nahar, MN; Mahtab, MA; Habib, S; Arafat, SM; Rahman, M; Hoque, M; Rahman, AJE Nahar (Bangladesh Medical Journal, 2014)
The aim of this study is to compare histology activity index (HAI) scores in patients with HBeAg positive and HBeAg negative CHB to see if there is any difference in severity of liver injury between these two types of HBV. We did percutaneous liver biopsies of 77 CHB patients. Serum HBeAg status were assessed in all study subjects. Of them, 37.66% patients (29/77) had HBeAg positive HBV infection, while the rest 62.33% (48/77) had HBeAg negative HBV infection. 22/48 (27.78%) patients with HBeAg negative CHB had mild to moderate CH (HAI score 4-12) and 26/48 (72.22%) patients had minimal CH (HAI score 1-3). In contrast, mild to moderate CH was seen in 19/29(72.23%) patients with HBeAg positive CHB. The study shows there is no correlation between the necro-inflammatory activity in the liver and HBeAg status in the ser um in patients with CHB. DOI: http://dx.doi.org/10.3329/bmj.v42i1.18970 Bangladesh Med J. 2013 Jan; 42 (1): 7-10